Decentralising Wage Bargaining in Germany - A Way to Increase Employment? - Wolfgang Ochel (Center for Economic Studies and ifo Institute (CESifo), 2003)
The area-wide wage agreement is at the centre of Germany's system of collective bargaining. In recent years, however, there has been a tendency towards the decentralisation of collective bargaining. Individual wage agreements have led to more moderate wage developments, whilst wage agreements with individual firms, and agreements at the production unit level have not had this moderating effect. On the other hand, collective bargaining has become more flexible. The further decentralisation of collective bargaining gives rise to objections based in constitutional law and to the resistance of employees and (in part) also of employers.
Keywords: 330